2002
DOI: 10.1038/sj.ejcn.1601379
|View full text |Cite
|
Sign up to set email alerts
|

Multiple coronary risk factors in healthy older Kuwaiti males

Abstract: Objective: The objective was to examine the percentage and severity of obesity and some common biochemical coronary heart disease (CHD) risk factors in a sample of healthy Kuwaiti adult males ! 45 y of age. We also sought to determine the percentage of males at increased risk due to the presence of multiple CHD risk factors. Design: The study was a cross-sectional study. Setting: The study was conducted in all men who underwent a mandatory job related physical examination or who sought to obtain retirement ben… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
39
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(42 citation statements)
references
References 23 publications
3
39
0
Order By: Relevance
“…Our study also showed over-consumption of Na and cholesterol at an early age, which may help to explain the high prevalence and early onset of CVD among Kuwaitis (5,6) . Additionally, the high Na intake is consistent ( 4 ) F ib r e ( 1 ) V it a m in E…”
Section: Discussionsupporting
confidence: 60%
“…Our study also showed over-consumption of Na and cholesterol at an early age, which may help to explain the high prevalence and early onset of CVD among Kuwaitis (5,6) . Additionally, the high Na intake is consistent ( 4 ) F ib r e ( 1 ) V it a m in E…”
Section: Discussionsupporting
confidence: 60%
“…The data were collected as part of the Kuwait National Nutrition Surveillance System (KNNS). The KNNS system has been described elsewhere (10,20) ; however, in brief, it includes children and adults from all geographical locations (governorates) of Kuwait. It includes measurements of weight and height, WC and cholesterol values in some subgroups.…”
Section: Methodsmentioning
confidence: 99%
“…On account of lifestyle changes associated with the transition in nutrition in the Arabian Gulf, resulting principally from rising incomes associated with the discovery and production of oil over the past few decades, obesity has increased dramatically (9,10) . El Bayoumy et al (11) found that the overall prevalence of overweight and *Corresponding author: Email bojack@umd.edu r The Authors 2010 obesity among men was 29?3 % and 14?9 %, respectively, (P , 0?001) and the prevalence of overweight and obesity among women was 32?1 % and 14?2 %, respectively (P , 0?001).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The Nutrition Administration of the Ministry of Health established the KNSS to continuously monitor the nutritional health status of the Kuwaiti population using a serial cross-sectional design. The analysis was restricted to adults aged 20 to 69 years who attended mandatory health examinations for registration for government employment or pensions (12) . All Kuwaiti citizens have virtually guaranteed employment and enjoy a retirement pension.…”
Section: Study Populationmentioning
confidence: 99%